ANALISIS PRODUKSI DAN USAHATANI JAMBU AIR (Syzygiumaqueum L) DI KECAMATAN NAMO RAMBE - Jefri Hedyanta Tarigan; Fandri Siburian; Roida Ervina Sinaga (Universitas Quality, 2021)
Analyze Productivity and farming watery rose apple (Syzygiumaqueum L.) in Namorambe district. The result of this research is to find out what the cost or coinage is used in the growing of watery rose apple, the large profit it gets, the attitude toward its farming and the analysis of factors that affect the profits of watery rose apple cultivation in Batu Penejemuran village. The plan used is using qualitative analyse by calculating and analyzing the y-ing data comes from the way interviews are told to honey watery rose apple farmer that total ten people who plant jambu air madu in Namo Rambe Deli Serdang regency. This reasearch has shown that thunder can be obtained at the larger scale of trafic, the lower production cost, total productivity and high market cost in the field when harvesting. The second year started to see a productivity of the can.